DAMPAK KEPEMIMPINAN SEBAGAI PENENTU KINERJA PEGAWAI KANTOR CAMAT LIMBOTO - Ishak, Olfin; Gani, Roydah; Yusuf, Nurdin (Gapenas Publisher, 2025)
This research aims to examine the impact of leadership in determining employee performance at the Limboto Sub-district Office, Gorontalo Regency. Using multiple linear regression analysis, the results showed that Directing and Coaching leadership styles have a significant positive effect on performance. However, Supporting and Delegating leadership styles showed a negative and insignificant effect, which can decrease employee performance. These styles are irrelevant to be applied at the Limboto Sub-district Office because they have the potential to reduce employee performance. This finding emphasizes the importance of improving employee performance by focusing on the Coaching leadership style, as it provides the most dominant contribution.